LONELINESS AND PSYCHOLOGICAL DISTRESS AMONG AFRICAN AMERICAN ASSISTED LIVING RESIDENTS APPROACHING END OF LIFE. (20th December 2022) - Arthur, Christopher; Bender, Alexis; Perkins, Molly
Abstract: Social isolation and loneliness are common at end of life and important contributors to psychological distress, particularly among older adults. Despite evidence that isolation and loneliness are generally prevalent in assisted living (AL), little research has examined these states within the context of end of life (EOL). This study uses secondary data from an EOL study in assisted living to qualitatively characterize the experience of isolation and loneliness in African American AL residents with varying levels of psychological distress. We performed a thematic analysis using ethnographic and interview data collected from 25 residents (64% female) in a large (90+ bed) all-African American AL community in metropolitan Atlanta. We assessed psychological distress using the PHQ-4 and used this measure in qualitative analysis to explore varying patterns of social isolation and loneliness across residents. Findings showed high variability in psychological distress based on PHQ-4 scores (range 0–12, mean = 3.5, SD = 3.75). Across themes of social isolation and loneliness, we compared experiences of residents with low and high psychological distress. The maintenance of agency in the face of isolation and loneliness was the predominant pattern among the low-distress group, while passive withdrawal was consistently identified among the high-distress group. We classified these themes in terms of individual interpersonal relationships characterized by self-isolation and negotiation of family connections, as well as AL community-level relationships characterized by the liminality of the lived AL experience. Results have important implications for multilevel interventions designed to reduce social isolation, loneliness, and psychological distress among this population.